Happy IP: replacing the law and economics justification for intellectual property rights with a well-being approach - Derclaye, Estelle; Taylor, Tim (Sweet & Maxwell, 2015)
E.I.P.R. 197 The dominant justification for intellectual property rights at least in the West and international treaties is utilitarian, and more precisely based on the Chicago School of Law and Economics (first section). However, this school of thought is both flawed and ideological (second section). Basing protection solely on the economic aspect of utility (i.e. income) has been increasingly challenged in recent years. We thus propose that intellectual property rights should be justified using a notion of utility based directly upon well-being, rather than using income as a proxy. We outline a theory-neutral approach to well-being that could be employed for this purpose (third section). Our proposal, like any and every other legal programme, cannot avoid being ideological (fourth section) but it avoids the flaws of the Law and Economics approach. It is also not paternalistic (fifth section).